2015
DOI: 10.1039/c5ra15109k
|View full text |Cite
|
Sign up to set email alerts
|

Predictive calculation of carbon dioxide solubility in polymers

Abstract: Novel calculation model of CO2 solubility in polymers using a hybrid intelligence algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…CO 2 solubility is the maximum CO 2 quantity that can solute in different solutions. Evaluation, prediction, and measurement of CO 2 solubility in different biodegradable polymers has become notable technology for engineers in various chemical applications such as extraction and generation of novel materials 10 14 . Biodegradable polymers are a particular type of polymers that collapse by bacterial dissolution process to eventuate in natural fluids such as CO 2 and N 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 solubility is the maximum CO 2 quantity that can solute in different solutions. Evaluation, prediction, and measurement of CO 2 solubility in different biodegradable polymers has become notable technology for engineers in various chemical applications such as extraction and generation of novel materials 10 14 . Biodegradable polymers are a particular type of polymers that collapse by bacterial dissolution process to eventuate in natural fluids such as CO 2 and N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…At the same year, Minelli and Sarti 34 measured solubility and permeability of CO 2 in various glassy polymers by considering diffusion coefficient as a kinetic factor. In 2015, different mathematical and theoretical approaches by Ting and Yuan 10 , Li et al 7 and Quan et al 12 were studied to estimate CO 2 properties including solubility. All of them showed that the CO 2 solubility has direct relation with pressure and reverse relation with temperature.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of machine learning (ML) as a powerful correlation tool, many data-driven models were built to predict various transport and thermophysical properties of polymeric materials [43][44][45][46][47][48]. Li et al [43] have built a backpropagation artificial neural network (ANN) to estimate the solubility of CO 2 and N 2 in polystyrene, and CO 2 in polypropylene.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al 31 proposed the mixed neural network solution calculation model by combining Kent-Eisenberg with ANN and realized the better prediction performance. Li et al [32][33][34][35][36][37][38] also proposed several dissolution prediction models by combining chaos theory and particle swarm algorithm with the clustering method, improved the ANN training algorithm, and obtained the better prediction accuracy and correlation.…”
Section: Introductionmentioning
confidence: 99%